The Performance of Axially Loaded, Fully Grouted Rock Bolts Based on Pull-Out Experiments Utilizing Fiber Optics Technology and Associated Numerical Modelling of Such Support Elements - Vlachopoulos, Nicholas; Cruz, Daniel; Tatone, Bryan Stanley Anthony; Lisjak, Andrea; Mahabadi, Omid K.; Forbes, Bradley; Carrapatoso, Carla (Geotechnical and geological engineering, 2020)
Rock bolt is a support system extensively utilized in Civil and Mining Engineering applications, especially for underground excavations projects. The main function of a rock bolt is to stabilize the rock mass around the opening of an excavation by fastening to further stable formations. Previous technical work developed pull-out testing in order to improve understanding regarding the mechanical response within this system. However, due to limitations with conventional laboratory methods of capturing strain, there still exists a lack of understanding in this mechanical response at the micro-scale; more specifically, in the detailed strain profile distribution along fully grouted rock bolts. Aiming to address this knowledge gap, two research programmes were conducted and will be addressed in this paper: numerical modelling of pull-out tests through finite element method (FEM) and hybrid finite-discrete element method (FDEM), and laboratory pull-out tests on concrete samples utilizing a newly developed distributed optical strain sensing technology that provides a spatial resolution of 0.65 mm in order to capture the strain along the rock bolt. Experimental and modelling results were compared to evaluate the numerical approaches feasibility and their correspondence with the experiments. FDEM modelling demonstrated ability in capturing general mechanical behavior, while the FEM software seems to be a good option to be utilized as a design tool, yet improvements to the interaction model are necessary to achieve a better calibration with experimental results.